FAKTOR-FAKTOR YANG MEMENGARUHI PEMBIAYAAN BERMASALAH PADA BANK UMUM SYARIAH DI INDONESIA - PUTRI, SILVIA; KUSUMANINGTIAS, ROHMAWATI (Jurnal Akuntansi AKUNESA, 2020)
This study aims to determine the effect of the quality of implementing GCG, size bank, distribution of murabahah financing, liquidity and profitability on non performing financing. The research sample is 10 Sharia Commercial Banks (BUS) registered at Bank Indonesia. This studies use multiple regression analysis. The result showed that the quality of implementing GCG in this study has a positive effect on non performing financing. However, size bank, distribution of murabahah financing, liquidity and profitability has no effect on non performing financing.